(untitled) (Ius Novum, 2024)
On January 1, 2024, the Act of July 7, 2023 on support benefits came into effect, which introduced a new type of benefit, the support benefit. The purpose of the publication is to present the essence of the newly introduced support benefit and to attempt to evaluate the adopted regulations. The authors also indicate the necessary directions of changes in the support system for people with disabilities, the main goal of which should be the empowerment of people with disabilities.